EPISTEMIC RATIONALITY IN ISLAMIC EDUCATION: The Significance for Religious Moderation in Contemporary Indonesian Islam - Prasetia, Senata Adi; Asrohah, Hanun; Najiyah, Siti Firqo; Arif, Syaiful (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This article discusses the concept of epistemic rationality in Islamic education and its significance for strengthening religious moderation in contemporary Indonesian Islam. The questions are: (1) How is the conception of epistemic rationality? (2) To what extent is the role of epistemic rationality in Islamic education? (3) How do classical Islamic treasures view the epistemic rationality and its significance for strengthening religious moderation in Indonesian Islam? Afterwards, the theoretical assumption underlying this article is that the strengthening of religious moderation without being supported by epistemic rationality is null and void. This article finds that the passion of reading in Islam processed through epistemic rationality has provided huge contribution for Islamic civilization so that it reaches its golden age. Hence, in Indonesian Islamic education context, strengthening religious moderation must be delivered through epistemic rationality as basic reasoning in understanding religious text and digging the diversity phenomenon in order to avoid radicalism and blind fanaticism. Epistemic rationality must be considered as starting point to build curriculum structure and learning contents that emphasize more on the competency of ‘know-how’ and ‘know-why’ rather than ‘know-what’.